Optimalisasi Corporate Social Responsibility Sebagai Upaya Dalam Mendukung Penerapan Prinsip Berkelanjutan Pada Korporasi - Elma Muthia Afnahanifa; Lastuti Abubakar; Tri Handayani (Nagari Law Review, 2021)
The role of corporations in applying sustainable principles cannot be separated from the commitment of corporations in carrying out social and environmental responsibility or corporate social responsibility (CSR). In practice, corporations must also have clear CSR commitments. However, the implementation of CSR in Indonesia has not been optimally carried out by corporations from a sustainable development perspective. Corporate Social Responsibility is still considered an obligation, it has not become a good character inherent in the corporation. This paper will discuss about the optimization of CSR in Indonesia by analyzing the normative legal measures that can be taken against the CSR legislation seen from the prospects and challenges that Indonesia has. The approach method used in this study is a normative juridical approach with descriptive analytical research specifications and analyzed by qualitative normative methods. The problem in managing CSR in Indonesia is that the concept of CSR is not aligned with sustainable principles. From this, an understanding can be drawn that basically the optimization that is felt to be the most appropriate when viewed from the existing gaps in CSR regulation is the making of pentahelix policies that involve the government, society, non-governmental organizations, academics, and the media.